2023
DOI: 10.3390/jcm12144620
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cannabidiol in Metabolic Syndrome—An Opportunity to Improve the Patient’s Health or Much Ado about Nothing?

Michał Wiciński,
Anna Fajkiel-Madajczyk,
Zuzanna Kurant
et al.

Abstract: Cannabis-derived therapies are gaining popularity in the medical world. More and more perfect forms of cannabinoids are sought, which could be used in the treatment of many common diseases, including metabolic syndrome, whose occurrence is also increasing. The purpose of this review was to investigate the usefulness of cannabinoids, mainly cannabidiol (CBD), in individuals with obesity, impaired glucose and lipid metabolism, high blood pressure, and non-alcoholic fatty liver disease (NAFLD). We summarised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…The main causes of such a situation are changes in lipid metabolism and the deposition of various lipid fractions such as sphingolipids. A similar conclusion was drawn by the Cinar et al, who found that in obese mice, intensified ceramide synthesis through the stimulation of the CB1 receptor in hepatocytes caused hepatic insulin resistance development [29,36].…”
Section: Discussionsupporting
confidence: 79%
“…The main causes of such a situation are changes in lipid metabolism and the deposition of various lipid fractions such as sphingolipids. A similar conclusion was drawn by the Cinar et al, who found that in obese mice, intensified ceramide synthesis through the stimulation of the CB1 receptor in hepatocytes caused hepatic insulin resistance development [29,36].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, CBD may cause hypotension and dizziness, which in certain instances could lead to falls and injuries [ 118 ]. CBD might also affect immune system function, although its exact mechanisms and clinical significance remain not entirely clear.…”
Section: Issues Should Be Considered In the Application Of Cbdmentioning
confidence: 99%